Employability and mobility of bachelor graduates in Europe key results of the Bologna process - Schomburg, Harald; Teichler, Ulrich (SensePublishers, 2011)
A decade after the Bologna Declaration has called for the establishment of a cycle system of study programmes and degrees all over Europe the changes actually having occurred in this reform process can be measured and assessed. To what extent did the bachelor students gained international experiences during or after their study program? What is the proportion of bachelor degree holders who are employed about one year after graduation? What are the labor market experiences of those bachelor graduates who started to work? Was it difficult to gain relevant employment? What are the employment conditions for bachelor graduates in terms of income, position, working time, unlimited term contracts compared to traditional graduates? To what extent are bachelor graduates working in areas with close relation to their field of study (horizontal match)? Is their level of education needed for their work tasks (vertical match)? These are the key questions which will be answered in this volume based on surveys of graduates from institutions of higher education recently undertaken in ten European countries (Austria, Czech Republic, France, Germany, Hungary, Italy, Norway, Netherlands, Poland, and United Kingdom). The bachelor-master-structure actually implemented varies substantially between the countries and also the consequences of these reforms differ strikingly. In some countries, more students spend a period of study abroad than the goal set for the year 2020 in the Bologna Process; in other countries, not yet a quarter of the expected rate is achieved. Also the frequency of bachelor graduates differs by country who opt for further study, transfer to employment or are both employed and students. The comparative study also provides a wealth of information about the employment and work situation of bachelor graduates as compared to other graduates from institutions of higher education. The book provides relevant information for students and teaching staff at institutions of higher education, employers and politicians and administrative staff dealing with higher education issues.